DIGITALISASI UMKM MELALUI PEMANFAATAN GOOGLE MAPS:STRATEGI PEMBERDAYAAN UMKM LOKAL DI DESA UJUNG TERAN KABUPATEN KARO - Mukhazza Albitha Alsha; Nur Asiyah Jamil Rangkuti; Putri Wahyuni; Sandi Nugraha; Safriaandy Safriaandy (Smart Education, 2025)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, especially in rural areas such as Ujung Teran Village, Karo Regency, which is rich in agricultural products but has limited market access. The main challenge is low digital literacy, which requires empowerment through technology such as Google Maps. This community service research examines the effectiveness of Google Maps as a digital marketing medium to increase the competitiveness of MSMEs. The method used a descriptive qualitative approach with field observations, in-depth interviews with 20-30 MSME owners, and training interventions and Google My Business (GMB) registration. The results showed an increase in online visibility, consumer reviews, and market reach, despite infrastructure constraints. The conclusion confirms that this strategy is effective in reducing the rural-urban economic gap, in line with the Industrial Revolution 5.0. Recommendations include continuous assistance and replication in similar areas for resilient MSMEs. This study contributes to community welfare and the study of MSME digitalization in Indonesia. Keywords: SMEs, Google Maps, marketing digitalization, rural empowerment, Karo Regency Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) berperan strategis dalam ekonomi Indonesia, khususnya di pedesaan seperti Desa Ujung Teran, Kabupaten Karo, yang kaya produk pertanian namun terbatas akses pasar. Tantangan utama adalah literasi digital rendah, sehingga diperlukan pemberdayaan via teknologi seperti Google Maps. Pengabdian pengabdian masyarakat ini mengkaji efektivitas Google Maps sebagai media digitalisasi pemasaran untuk meningkatkan daya saing UMKM. Metode menggunakan pendekatan kualitatif deskriptif dengan observasi lapangan, wawancara mendalam kepada 20-30 pemilik UMKM, dan intervensi pelatihan serta pendaftaran Google My Business (GMB). Hasil menunjukkan peningkatan visibilitas online, ulasan konsumen, dan jangkauan pasar, meski ada hambatan infrastruktur. Kesimpulan menegaskan strategi ini efektif mengurangi kesenjangan ekonomi pedesaan-perkotaan, sejalan dengan Revolusi Industri 5.0. Rekomendasi meliputi pendampingan berkelanjutan dan replikasi di daerah serupa untuk UMKM tangguh. Pengabdian ini berkontribusi pada kesejahteraan masyarakat dan kajian digitalisasi UMKM di Indonesia. Kata kunci: UMKM, Google Maps, digitalisasi pemasaran, pemberdayaan pedesaan, Kabupaten Karo